THE NARRATIVE DISCOURSE OF INTERETHNIC BEHAVIOURS AND RELATIONS: THE CONTESTATION OF ETHNIC IDENTITY - Widyastuti, Susana (LITERA, 2019)
Drawing from Discursive Social Psychology (DSP) (Potter, 1998; Potter Edwards, 2001), this study is concerned with how attitudes, behaviours, and identity can be observed through language in use or discourse. Focusing on the narratives of the marginalized Chinese Indonesians, it particularly aims at revealing behaviours in coping with the majority group, and how such behaviours may in turn shape intergroup relations and ethnic identity. The data were in the form of narratives of personal experience of Chinese Indonesians collected through interview which were then scrutinized through in-depth analysis within their socio-political context. It has been revealed that in dealing with unequal power relations, two behaviours are embraced – convergence and divergence – which are manifested in various discursive and social practices of adapting to the wider society and maintaining aspects of ethnic identity. Any choice of behaviours can have consequences for interethnic relations and ethnic identity. The ideological power exercised by different regimes has obviously constructed ethnic identity and thus made it historically and ideologically contested. The contestation is discursively articulated through the negotiation between ethnic and national identity, the labelling practice using the words Cina and Tionghoa, and the perpetuation of stereotypes associated with the ethnic group. Keywords:  ethnicity, discourse, identity, social-psychology